2014
DOI: 10.1007/s11695-014-1496-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of Weight Loss Reporting After Gastric Bypass and Sleeve Gastrectomy Using BOLD Data 2008–2011

Abstract: For ease and accuracy of comparison, the percentage of initial body weight or percentage of total weight loss should be used for the expression of weight loss after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 21 publications
6
17
0
3
Order By: Relevance
“…Studies have demonstrated that even when looking at a single weight loss surgery such as GB, greater preoperative BMI is associated with decreased excess body weight loss [37], however with no significant difference in total body weight loss [38]. Our own analysis confirmed that weight loss differences at 6–24 months remained highly significant when adjusted for baseline BMI.…”
Section: Discussionsupporting
confidence: 71%
“…Studies have demonstrated that even when looking at a single weight loss surgery such as GB, greater preoperative BMI is associated with decreased excess body weight loss [37], however with no significant difference in total body weight loss [38]. Our own analysis confirmed that weight loss differences at 6–24 months remained highly significant when adjusted for baseline BMI.…”
Section: Discussionsupporting
confidence: 71%
“…There is significant heterogeneity in previous studies as to whether baseline BMI is associated with better or worse outcomes depending on whether %EWL or %TWL is used [20], but in general %TWL is preferred as the outcome measure in long-term studies of bariatric surgery if one wishes to reduce variability based on initial BMI [21, 22]. Our data support a conclusion that higher BMI is associated with improved long-term %TWL following GB but a lower rate of achieving BMI < 30 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint was percentage of total weight loss (%TWL) at 12 months. The weight loss indices among RYGB and SG patients within BOLD have been studied previously; %TWL was determined to be the most accurate and least influenced by initial weight and was suggested to be used for the expression of weight loss after surgery [24]. The secondary endpoints were disease resolution for DM, HTN, GERD, HLD, and OSA at 12 months, as well as 30-day postoperative safety.…”
Section: Methodsmentioning
confidence: 99%